Peran Inklusi Keuangan dalam Meningkatkan Keberlanjutan UMKM Sektor Makanan di Kota Makassar - Muliati Abbas; Nurfatwa Andriani Yasin; Andi Nur Insan (Movere Journal, 2026)
This study aims to analyze the role of financial inclusion in enhancing the sustainability of food-sector MSMEs in Makassar City. The research adopts a quantitative approach with an explanatory design. Primary data were collected through a survey of 100 food-sector MSME owners selected using purposive sampling. Data analysis was conducted using Pearson correlation analysis to identify the strength of the relationships between the dimensions of financial inclusion and MSME sustainability. The results indicate that digital finance has a positive, strong, and significant relationship with MSME sustainability (r = 0.793; p < 0.01). In contrast, financial services, the use of financial products, as well as the quality and affordability of financial services show weak and insignificant relationships with MSME sustainability. These findings suggest that the utilization of digital financial services plays a more substantial role in supporting MSME sustainability than mere access to conventional financial services.